Orodispersible Film Loaded with Enterococcus faecium CRL183 Presents Anti-Candida albicans Biofilm Activity In Vitro - Virgínia Barreto Lordello; Andréia Bagliotti Meneguin; Sarah Raquel de Annunzio; Maria Pía Taranto; Marlus Chorilli; Carla Raquel Fontana; Daniela Cardoso Umbelino Cavallini (MDPI AG, 2021)
Background: Probiotic bacteria have been emerging as a trustworthy choice for the prevention and treatment of Candida spp. infections. This study aimed to develop and characterize an orodispersible film (ODF) for delivering the potentially probiotic Enterococcus faecium CRL 183 into the oral cavity, evaluating its in vitro antifungal activity against Candida albicans. Methods and Results: The ODF was composed by carboxymethylcellulose, gelatin, and potato starch, and its physical, chemical, and mechanical properties were studied. The probiotic resistance and viability during processing and storage were evaluated as well as its in vitro antifungal activity against C. albicans. The ODFs were thin, resistant, and flexible, with neutral pH and microbiologically safe. The probiotic resisted the ODF obtaining process, demonstrating high viability (>9 log10 CFU·g−1), up to 90 days of storage at room temperature. The Probiotic Film promoted 68.9% of reduction in fungal early biofilm and 91.2% in its mature biofilm compared to the group stimulated with the control film. Those results were confirmed through SEM images. Conclusion: The probiotic ODF developed is a promising strategy to prevent oral candidiasis, since it permits the local probiotic delivery, which in turn was able to reduce C. albicans biofilm formation.